2011
DOI: 10.1111/j.1468-2338.2010.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative and qualitative analysis of sexual harassment claims 1995-2005

Abstract: This article explores the organisational and legal context in which parties involved in claims relating to sexual harassment operate, and presents an analysis of the population of sexual harassment cases heard by Employment Tribunals between 1995 and 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This research found that only 14% of workers who took legal action used formal grievance procedures in an attempt to avoid recourse to legal action. Furthermore, research by Lockwood et al (2011) into sexual harassment litigation found that claimants' chances of success were heightened if an internal complaint had been made prior to commencing legal action.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This research found that only 14% of workers who took legal action used formal grievance procedures in an attempt to avoid recourse to legal action. Furthermore, research by Lockwood et al (2011) into sexual harassment litigation found that claimants' chances of success were heightened if an internal complaint had been made prior to commencing legal action.…”
Section: Resultsmentioning
confidence: 97%
“…One plausible explanation for multiple claims might relate to the costs of filing claims (which may encourage claimants to maximize the number of claims made in a case) and also to the particular nature of MHD, which often results in dismissal and people feeling victimised. However, it should be noted that the number of multiple claims is considerably lower in respect of disability than in the case of other jurisdictions; for example, in sexual harassment claims, 80% of cases included at least one additional complaint (Lockwood, Rosenthal, & Budjanovcanin, 2011). One reason for this might be that in disability discrimination a significant number of claims are brought by claimants who believe they were denied employment because of disability, rather than because of discrimination during employment.…”
Section: (Ii) Number Of Additional Legal Claims Broughtmentioning
confidence: 88%
See 1 more Smart Citation
“…that MHD is not claimed in the absence of other claims) requires further comment. One plausible explanation for multiple claims might relate to the costs of filing claims, which may encourage claimants to maximize the number of claims made in a case (Lockwood et al, 2011). Another explanation might be the particular nature of MHD, which often results in dismissal and people feeling victimized.…”
Section: Legal Issues In Eat Casesmentioning
confidence: 99%
“…However, it should be noted that the number of multiple claims is considerably lower in respect of disability than in the case of other jurisdictions. For example, 80% of cases in sexual harassment claims included at least one additional complaint (Lockwood et al, 2011). One reason for this might be that in disability discrimination, a significant number of claims come from claimants who believe they were denied employment because of disability, rather than arising from discrimination during employment.…”
Section: Legal Issues In Eat Casesmentioning
confidence: 99%